Spatial-temporal distribution, metallogenic mechanisms and genetic types of nephrite jade deposits in China - Zhang, Cun; Yang, Fan; Yu, Xiaoyan; Liu, Jinhai; Carranza, Emmanuel John M.; Chi, Jie; Zhang, Peng (Frontiers in Earth Science, 2023)
The nephrite jade deposits of different tectonic units in China exert significant commercial quality, which have attracted wide attention. However, these deposits have not been systematically summarized to date. Here, we investigate the major nephrite jade deposits in China to decipher their gemological and mineralogical characteristics, spatial-temporal distribution, and mineralization processes as well as to identify their geological settings and gemological properties, via integrating published geochronology, major and trace elements as well as H-O isotopes. The compiled data suggest that the major nephrite jade deposits in China can also be generally divided into green jade-type (GJ-type) and white jade-type (WJ-type), but most of them belong to the latter. The GJ-type nephrite deposits predominantly occur in ophiolite/ophiolitic mélange suites or are embedded into ultramafic serpentine jade orebodies. This type of nephrite jade mainly formed through the late auto-metamorphic metasomatism of serpentine or the spontaneous crystallization/precipitation along suture/shear zones that acted as pathways to migrate Ca-rich fluids during orogeny. In contrast, the orebodies of WJ-type nephrite jade are usually hosted at the contact zones between the dolomitic marbles and intermediate-felsic or mafic intrusive rocks, which were produced through metamorphism-metasomatism during post continent-continent collision, such as the Kunlun orogenic belt with about ~1300 km Hetian nephrite belt, and the eastern nephrite jade deposits along the Pacific Ocean. Our study highlights that the nephrite jade deposits in China originally formed during multiple tectonic stages related to the interactions between hydrothermal fluids and metamorphism under subduction accretion- and collision orogenesis-related settings. In addition, this study also provides insights into the genetic discrimination, mineral exploration, and occurrence characteristics of nephrite jade deposits as well as the evaluation and identification of nephrite jade quality.